2002
DOI: 10.1016/s0893-133x(02)00325-1
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Decreases Bradykinesia-rigidity in Haloperidol-treated Patients with Schizophrenia

Abstract: We applied nicotine 21 mg and matching placebo transdermal patches to thirty haloperidol-treated patients with schizophrenia who smoked. Clinical assessments of bradykinesia-rigidity were lower during nicotine patch administration than during placebo patch administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…The positive correlation between mGluR5 and antipsychotic use that we found in nonsmokers seems to support the selfmedication hypothesis with regard to medication side effects. In haloperidol-treated patients with schizophrenia, the application of nicotine through transdermal patches reduced bradykinesia-rigidity (Yang et al, 2002). Because the majority of subjects included in our study used atypical antipsychotics, one might conclude that this nicotine effect is irrelevant.…”
Section: Discussionmentioning
confidence: 86%
“…The positive correlation between mGluR5 and antipsychotic use that we found in nonsmokers seems to support the selfmedication hypothesis with regard to medication side effects. In haloperidol-treated patients with schizophrenia, the application of nicotine through transdermal patches reduced bradykinesia-rigidity (Yang et al, 2002). Because the majority of subjects included in our study used atypical antipsychotics, one might conclude that this nicotine effect is irrelevant.…”
Section: Discussionmentioning
confidence: 86%
“…This is consistent with the hypothesis of Mancuso et al (1999), whereby the nicotine-induced improvement in attention is a consequence of nicotine acting to 'lock the brain into the attentional processing mode and so there are fewer lapses in attention', hence fewer errors of omission might be expected. However, an improvement in accuracy (proportion correct) following nicotine administration has also been observed in subjects displaying impaired attentional function, associated with schizophrenia, Alzheimer's disease, and attention deficit hyperactivity disorder (White and Levin, 1999;Shytle et al, 2002;Yang et al, 2002). The 5-CSR task was developed to examine sustained attention in rodents (Carli et al, 1983) and is regarded as being analogous to the CPT (Jones and Higgins, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that nicotine can lock the brain into an attentional processing mode whereby there are fewer lapses in attention and therefore less omissions (Mancuso et al, 1999). These observations may underlie the ability of nicotine to enhance attention and improve the symptomatology of various human diseases including schizophrenia (Yang et al, 2002), Alzheimer's disease (White and Levin, 1999), attention deficit hyperactivity disorder (Shytle et al, 2002), Parkinson's disease (O'Neill et al, 2002), and Tourette's syndrome (Sanberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this phenomenon has been demonstrated with one currently indicated treatment for schizophrenia, clozapine, as discussed in the next section. Yang et al (2002) Nicotine patch improves tremor and bradykinesia-rigidity symptoms in smokers with schizophrenia. Smith et al (2002) Smoking cigarettes does not increase tardive dyskinesia, extrapyramidal or parkinsonian symptoms.…”
Section: Nicotine As a Prototypic Agonistmentioning
confidence: 99%